The CXC Chemokine Receptor 3 Inhibits Autoimmune Cholangitis via CD8+ T Cells but Promotes Colitis via CD4+ T Cells - Liu, Qing-Zhi; Ma, Wen-Tao; Yang, Jing-Bo; Zhao, Zhi-Bin; Yan, Kai; Yao, Yuan; Li, Liang; Miao, Qi; Gershwin, M. Eric; Lian, Zhe-Xiong (Frontiers in Immunology, 2018)
CXC Chemokine Receptor 3 (CXCR3), a receptor for the C-X-C motif chemokines (CXCL) CXCL9, CXCL10, and CXCL11, which not only plays a role in chemotaxis, but also regulates differentiation and development of memory and effector T cell populations. Herein we explored the function of CXCR3 in the modulation of different organ-specific autoimmune diseases in IL-2 receptor deficiency (CD25-/-) mice, a murine model for both cholangitis and colitis. We observed higher levels of CXCL9 and CXCL10 in the liver and colon and higher expression of CXCR3 on T cells of the CD25-/- mice compared with control animals. Deletion of CXCR3 resulted in enhanced liver inflammation but alleviated colitis. These changes in liver and colon pathology after CXCR3 deletion were associated with increased numbers of hepatic CD4+ and CD8+ T cells, in particular effector memory CD8+ T cells, as well as decreased T cells in mesenteric lymph nodes and colon lamina propria. In addition, increased IFN-γ response and decreased IL-17A response was observed in both liver and colon after CXCR3 deletion. CXCR3 modulates the functions of T cells involved in different autoimmune diseases whereas the consequence of such modulation is organ-specific regarding to their effects on disease severity. Our findings emphasize the importance of extra caution in immunotherapy for organ-specific autoimmune diseases, as therapeutic interventions aiming at a target such as CXCR3 for certain disease could result in adverse effects in an unrelated organ.